(untitled) (Journal of Asian Development Studies, 2024)
This paper analyses the relationship among eco-philosophy, praxis, and the deconstruction of anthropocentrism in Powers’ (2019) The Overstory, utilizing the theoretical framework of Deep Ecology as advanced by Arne Naess (1989). Powers’ work challenges the prevailing anthropocentric perspective, presenting an eco-realm in which trees and ecosystems serve as primary protagonists, questioning the hierarchical distinction between humans and nature. This study, informed by Naess’s concepts of Deep Ecology, such as intrinsic value, ecological self-realization, and biocentric equality, examines how The Overstory (2019) promotes a transition from anthropocentric ethics to a life-centered environmental ethos. The study examines the praxis derived from Power’s narrative, highlighting the novel’s advocacy for environmental action, shared responsibility, and a redefinition of humanity’s position within the biosphere. It emphasizes the metamorphic capacity of the story in cultivating ecological awareness, suggesting that the novel acts as a medium for reevaluating, redefining ecological ethics, and prompting action against environmental degradation. This study argues that by integrating Naess’s (1989) theoretical framework with literary analysis, the novel challenges anthropocentrism while proposing a realistic approach to biocentric life, encouraging readers to adopt ecological interdependence and activism. Integrating the ecophilosophy of deep ecology and practice highlights the novel’s importance in contemporary environmental discourse.